(untitled) (International Journal of Physiotherapy, 2016)
Background: The prevalence of type 2 diabetes mellitus has been on the increase both in high and medium/low income countries. This increase is associated with health and economic consequences, especially in low sub-Saharan Africa that is resource stricken. Availability of affordable and easy to implement treatment intervention will surely reduce these health and economic sequealae of type 2 diabetes mellitus. This study was carried out to investigate the effects of plyometric exercise on concomitants of fitness and metabolic profile in type 2 diabetes patients. Methods: Simple random sampling technique was employed to recruit participants (n=27) for this study after meeting the inclusion criteria. Physical and physiological measurements were taken from the participants before and after six weeks of plyometric exercise for the experimental group and the control who did not participate in plyometric exercise. Results: A total number of twenty seven (control= 13) participated in the study and there are not significant differences in the physical and physiological parameters of the two groups. There are significant differences in the physiological parameter after six (6) weeks of plyometric exercise among the experimental groups while there are no significant differences among the control group. The eta squared statistics of few parameters show that the effect sizes range between medium and large association. Conclusion: It is concluded that among the concomitants of fitness, plyometric exercise is effective only in improving muscle fitness and body composition.